HỘI CHỨNG TAKOTSUBO TRÊN NGƯỜI BỆNH CÓ TIỀN SỬ RỐI LOẠN LO ÂU: BÁO CÁO CA LÂM SÀNG (Vietnam Journal of Community Medicine, 2026)
Background: Takotsubo Syndrome (TTS), also known as "Broken Heart Syndrome," is a stress-induced cardiomyopathy that mimics acute coronary syndrome. Although generally reversible, TTS can lead to severe acute heart failure, particularly in patients with underlying psychological disorders.Case presentation: A 65-year-old female with a history of anxiety disorder was admitted with acute chest pain and dyspnea following a recent emotional stressor. Laboratory investigations revealed elevated cardiac biomarkers, and electrocardiography demonstrated ST-segment elevation in leads V1–V4. Transthoracic echocardiography on admission showed the typical pattern of apical ballooning with severely reduced left ventricular ejection fraction (33%). Coronary angiography excluded significant obstructive coronary artery disease. The patient was diagnosed with Takotsubo syndrome and managed with optimal medical therapy along with psychological support. At the 2-year follow-up, clinical symptoms remained stable, and cardiac function had fully normalized.Conclusion: This case highlights the necessity of differential diagnosis for TTS in postmenopausal women and the importance of managing anxiety disorders in holistic patient care.
Keywords: Takotsubo Syndrome, Acute heart failure, Anxiety disorder, Apical ballooning.